Rola pól doświadczalnych w rozwoju rolnictwa Królestwa Polskiego i ziem zabranych w XIX i początkach XX wieku - Biały, Halina (Zeszyty Wiejskie, 2013)
In the 19th and early 20th century the Polish Kingdom underwent many important changes that influenced the development of its agricultural economy. Those changes included the introduction for cultivation of new varieties of plants nd changes in the methods of soil fertilization. Agrotechnical progress would have been impossible without organizing experimental fields which played an important role in the lives of the farmers concerned. This article attempts to demonstrate that field experiments were conducted in the Polish Kingdom and the lands removed from its territory in the 19th and early 20th century. It describes the space devoted to this type of experiments as well as the organizers of these important agronomic projects. The article also presents Instrukcja dla doświadczeń polowych (“Instructions for field trials”) divided into two parts. The first part introduces the general principles followed in setting up experimental fields, while the second part refers to the use of chemical fertilizers. Works carried out on various fields, namely: the choice of location, soil testing, fertilization, sowing, weeding and collection of crops are also discussed.